Autism Spectrum Disorder in a Girl with a De Novo X;19 Balanced Translocation - Marcelo Razera Baruffi; Deise Helena de Souza; Rosana Aparecida Bicudo da Silva; Ester Silveira Ramos; Danilo Moretti-Ferreira (Case Reports in Genetics)
Balanced X-autosome translocations are rare, and female carriers are a clinically heterogeneous group of patients, with phenotypically normal women, history of recurrent miscarriage, gonadal dysfunction, X-linked disorders or congenital abnormalities, and/or developmental delay. We investigated a patient with a de novo X;19 translocation. The six-year-old girl has been evaluated due to hyperactivity, social interaction impairment, stereotypic and repetitive use of language with echolalia, failure to follow parents/caretakers orders, inconsolable outbursts, and persistent preoccupation with parts of objects. The girl has normal cognitive function. Her measurements are within normal range, and no other abnormalities were found during physical, neurological, or dysmorphological examinations. Conventional cytogenetic analysis showed a de novo balanced translocation, with the karyotype 46,X,t(X;19)(p21.2;q13.4). Replication banding showed a clear preference for inactivation of the normal X chromosome. The translocation was confirmed by FISH and Spectral Karyotyping (SKY). Although abnormal phenotypes associated with de novo balanced chromosomal rearrangements may be the result of disruption of a gene at one of the breakpoints, submicroscopic deletion or duplication, or a position effect, X; autosomal translocations are associated with additional unique risk factors including X-linked disorders, functional autosomal monosomy, or functional X chromosome disomy resulting from the complex X-inactivation process.